(untitled) (Research, Society and Development, 2024)
Gestational Diabetes Mellitus (GDM) is a condition diagnosed in pregnancy, with important impacts on maternal and fetal health in the short and long term. Pregnant women with DMG have a higher risk of immediate complications, such as hypertensive disorders, polydramnios and the need for cesarean sections, especially in cases of early diagnosis. In the long term, DMG significantly increases the risk of type 2 Diabetes Mellitus (DM2), metabolic syndrome and cardiovascular diseases, with up to 60% of affected women developing DM2. Despite this, only half of them are screened for DM2 in the postpartum period. For the fetus, DMG is associated with macrosomy, neonatal hypoglycemia, respiratory distress syndrome and hypertrophic cardiomyopathy in the short term. In the long term, exposure to the hyperglycemic environment increases the risk of obesity, DM2 and cardiovascular diseases in the offspring. The objective of this article is to explore the main complications for mother and newborn associated with DMG through a narrative bibliographic review study. Adequate diagnosis and glycemic control during pregnancy are crucial to reduce immediate complications and improve future outcomes for mother and child.